EFFECTIVE STEPS OF IDENTIFYING AND CONSTRUCTING RESEARCH PROBLEMS - Agung Budi Kurniawan; Dwi Rahayu; Indah Puspitasari (Jurnal Humaniora, 2017)
Research problem is one of the most important parts in a research. It is placed in the beginning of research writing especially after background and identification of problem. Research problem determines researchers’ action, theories, and technique of collecting and analyzing data, findings, analysis, conclusion, and overall research implementation. It seems the central point of a scientific research. Based on our research, we find that there 2 criteria of research problems; first, it is discovered and second, it is invented or created. Every research topic and research design has specific research problem. On the other hand, we also find 2 types of research problem technically which are finding research problem and analysis research problem. Our concern in this scientific article is to present one of our research finding and analysis which is 7 effective steps of constructing research problems. Every step is connected to one another till the last step of identifying or constructing research problems. Our main discussion is that research problem is the last product from previous problem delivered in the research topic, background of the study, identification of the problems, and the influence of research design. In conducting the research, we take 40 S-1English thesis of English education study program of STKIP PGRI Pacitan in the academic year 2014-2015 by using purposive sampling technique. We applied descriptive qualitative approach based on coherence analysis. We expect the presentation of our research findings and analysis could be used as one reference for researchers to identify and construct research problems.